Legal Responsibility of Perpetrators of The Criminal Act of Aggravated Theft (Study of Decision No. 47/Pid.B/2022/Pn Lbo) - Benyamin Ginano, Raihan Gautama; Gunarto, Gunarto (UNISSULA Semarang, 2025)
This study aims to analyze the legal aspects of aggravated theft in the context of social justice, focusing on Case Number 47/Pid.B/2022/PN Lbo. It examines the application of criminal sanctions against the perpetrator and considers the judge's perspective in delivering the verdict. The research addresses two main questions: first, how are criminal sanctions applied in this case, and second, how do the judge's considerations reflect the values of social justice. Employing a descriptive analytical method, this study explores the legal dimensions of aggravated theft within the specified case. The findings underscore the importance of a social justice-based approach in law enforcement, which emphasizes not only punishment but also rehabilitation and crime prevention, in order to create a more equitable and effective justice system.